2013
DOI: 10.1002/hyp.9951
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of precipitation and extreme events on the Loess Plateau of China between 1957 and 2009

Abstract: Abstract:Spatiotemporal trends in precipitation may influence vegetation restoration, and extreme precipitation events profoundly affect soil erosion processes on the Loess Plateau. Daily data collected at 89 meteorological stations in the area between 1957 and 2009 were used to analyze the spatiotemporal trends of precipitation on the Loess Plateau and the return periods of different types of precipitation events classified in the study. Nonparametric methods were employed for temporal analysis, and the Krigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…The non-parametric Mann-Kendall trend test (MK) was applied to analyze the temporal variations in extreme events because it is simple, robust method that addresses missing values and values below the examination threshold (Fu et al, 2004;Wan et al, 2013;Zhang et al, 2011b). The method has been recommended by the World Meteorological Organization (WMO) as a standard procedure for examining trends in hydrometeorological data that are serially independent (Hamed and Ramachandra Rao, 1998).…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-parametric Mann-Kendall trend test (MK) was applied to analyze the temporal variations in extreme events because it is simple, robust method that addresses missing values and values below the examination threshold (Fu et al, 2004;Wan et al, 2013;Zhang et al, 2011b). The method has been recommended by the World Meteorological Organization (WMO) as a standard procedure for examining trends in hydrometeorological data that are serially independent (Hamed and Ramachandra Rao, 1998).…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
“…In China, trends in extreme precipitation have been documented in several studies, which showed that the occurrence of precipitation extremes increases at the national scale and exhibits apparent regional differences Liu et al, 2014;Liu et al, 2013;Qian et al, 2007;Su et al, 2008;Wan et al, 2013;Wang et al, 2013;Wang et al, 2008;Yang et al, 2008;You et al, 2008;Zhai et al, 1999;Zhang et al, 2011a). For example, Qian et al (2007) found that the frequencies of extreme rain events increased in eastern China centered on the middle-lower reaches of the Yangtze River but decreased in North China and Southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…Monthly precipitation data were obtained from the State Meteorology Bureau of China. Monthly precipitation data are spatially interpolated using the ordinary Kriging method (Wan et al, 2011). The area-weighted method is used to compute the monthly precipitation in each catchment.…”
Section: Data Descriptionmentioning
confidence: 99%
“…This method has the advantages of not requiring a given data distribution and not being affected by outlying data, and has been used entensively to test trends in hydrometeorological data, including temperature, rainfall and runoff time series [13][14][15][16]. In this study, the M-K method was used to test the trend stability of extreme precipitation time series.…”
Section: Stability Testmentioning
confidence: 99%